Casuística de histiocitoma y enfermedades secundarias en un canino mestizo - Rojas M., Carolina (2020)
The case of a female mongrel dog, castrated, 1.5 years old with abnormal structures on the ear, in addition to alopecia and generalized pruritus is presented. The paraclinical aids performed were suggestive for cutaneous histiocytoma in addition to demodicosis. Surgical excision was performed, without observation of subsequent recurrences.